Recognition and value of submerged prehistoric landscape resources in Australia. (15th June 2018) - Ward, I.; Smyth, D.; Veth, P.; McDonald, J.; McNeair, S.
Abstract: Maritime cultural heritage is not just restricted to shipwrecks, historic waterfronts and contemporary Indigenous associations with marine and coastal areas, but also includes Indigenous coastal and submerged prehistoric archaeological sites and landscapes. For most of the 65, 000 years or so of human occupation in Australia, sea level has been lower than present, yet we know almost nothing about submerged landscapes and their associated cultural heritage. Improved mapping of the physical continental shelf is providing an insight into these landscapes from a geomorphological perspective but the prehistoric cultural potential is as yet unrealised. The unknown nature of this record means that it is overlooked in any pre-development assessment along the intertidal and offshore zones. The result is the potential damage or loss of maritime prehistoric cultural resources, and unrealized socioeconomic benefit. Focused on Western Australia, this article aims to raise awareness of this unrecognised cultural resource, with a view towards developing a more inclusive policy and one that specifically involves Traditional Owners in the protection of maritime cultural heritage in Australia. This is particularly apposite given seascapes are increasingly included in Native Title determinations, Indigenous Protected Areas and co-managed marine parks across Australia. Highlights: The 65 ka record of cultural landscapes on Australia's continental shelf is largely unrecognised. Theoretical studies and high-resolution imagery of the seabed highlight this potential. Seascapes are part of a common humanity for both Indigenous and non-Indigenous people. Collaboration between stakeholder and interest groups will improve discovery of these seascapes. Clearer involvement of Indigenous people in marine heritage is needed.